IMPLEMENTATION OF LEARNING READINESS COMMUNICATION BETWEEN CLASS TEACHERS AND PARENTS IN AN EFFORT TO IMPROVE TEACHERS' PEDAGOGIC COMPETENCE (INTERNATIONAL SEMINAR, 2025)
This article discusses the implementation of learning readiness communication between homeroom teachers and parents as an effort to improve teachers' pedagogical competence. This study aims to analyze the role of school-parent communication in strengthening students' learning readiness and its contribution to teachers' professional development. The method used is library research by reviewing various relevant scientific literature, including national and international journals, books, and previous research results. The results of the study indicate that effective communication between homeroom teachers and parents plays a crucial role in building students' learning readiness, increasing motivation, independence, and academic achievement. In addition, intensive interaction with parents enriches teachers' understanding of student characteristics, thus developing their pedagogical competence through the implementation of more adaptive learning strategies. The discussion also emphasizes that communication barriers, such as socioeconomic differences and limited digital literacy, need to be addressed with an inclusive and innovative approach. In conclusion, the implementation of learning readiness communication between homeroom teachers and parents is not only a means of supporting learning but also a strategic foundation for improving the quality of education. School-parent collaboration has been shown to have a positive impact on students' learning readiness while strengthening teachers' pedagogical capacity.